Karakteristik Pasien dengan Benda Asing Esofagus di RSUP Prof. Dr. R. D. Kandou Manado - Karokaro, Yose L. F. H.; Mengko, Steward K.; Najoan, Rizki R. (e-CliniC, 2026)
Abstract: Esophageal foreign bodies represent a medical emergency that may lead to serious complications in adults and children. Esophagoscopy serves as the main modality for identifying the location and removing the foreign body, either using rigid or flexible instruments. This study aimed to determine the characteristics of patients with esophageal foreign bodies at Prof. Dr. R. D. Kandou General Hospital Manado. This was a descriptive and retrospective study using medical record data of patients diagnosed with esophageal foreign bodies at Prof. Dr. R. D. Kandou General Hospital Manado for the years 2020–2024. The results showed that out of 56 samples, 55.35% were male patients. The highest percentages were found in childhood age group (48.21%), odynophagia (32.14%), and dysphagia (30.36%) as the primary symptoms, inorganic foreign bodies (85.71%), and cervical esophagus (80.36%) as the site of impaction. Rigid esophagoscopy was the most commonly used extraction method (96.42%). In conclusion, esophageal foreign bodies are more commonly found in males, predominantly in children. Odynophagia was the most frequently reported symptom. Most foreign bodies causing impaction were inorganic in nature, and the cervical esophagus was the most common site of lodgment. Rigid esophagoscopy remains the primary modality used in management. Keywords: esophageal foreign body; esophagoscopy management; rigid esophagoscopy   Abstrak: Benda asing esofagus merupakan salah satu kegawatdaruratan medis yang berpotensi menimbulkan komplikasi serius baik pada anak maupun dewasa. Esofagoskopi menjadi modalitas utama dalam menentukan lokasi dan sekaligus mengekstraksi benda asing, baik dengan esofagoskopi kaku maupun fleksibel. Penelitian ini bertujuan untuk mengetahui karakteristik pasien dengan benda asing esofagus di RSUP Prof. Dr. R. D. Kandou Manado. Jenis penelitian ialah deskriptif retrospektif, menggunakan data rekam medis pasien dengan diagnosis benda asing esofagus di RSUP Prof. Dr. R. D. Kandou Manado periode 2020-2024. Hasil penelitian mendapatkan 56 sampel penelitian; 55,35% ialah pasien laki-laki. Persentase tertinggi didapatkan pada kelompok usia anak-anak (48,21%), gejala utama odinofagia (32,14%) dan disfagia (30,36%), jenis benda asing anorganik (85,71%), lokasi impaksi pada segmen servikal (80,36%), dan esofagoskopi kaku sebagai metode ekstraksi (96,42%). Simpulan penelitian ialah kejadian benda asing esofagus lebih sering ditemukan pada laki-laki, terutama kelompok usia anak-anak, dengan keluhan odinofagia, benda asing anorganik, lokasi pada segmen servikal esofagus, dan penatalaksanaan menggunakan esofagoskopi kaku. Kata kunci: benda asing esofagus; tatalaksana esofagoskopi; esofagoskopi kaku